Analisis Peran Guru dalam Pembinaan Sikap Sosial Siswa di SD Laboratorium UNG - Sulmin; Thamrin A. Kum; Yusraningsih H. Pongoliu (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study is motivated by the presence of social attitude problems among elementary school students, such as lack of cooperation, low empathy, and impolite behavior. Therefore, the role of teachers is crucial in fostering students’ social attitudes. This study aims to describe the role of teachers in developing students’ social attitudes at SD Laboratorium UNG. This research employed a qualitative approach with a descriptive design. The subjects included the principal, teachers, and students of grades III, IV, and V. Data were collected through observation, interviews, and documentation. Data analysis used the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The results show that teachers play a significant role in fostering social attitudes through modeling, habituation, guidance, and reinforcement. The social attitudes developed include honesty, discipline, responsibility, tolerance, cooperation, politeness, social care, and self-confidence. Overall, students’ social attitudes show positive development, although some students still require further guidance. Thus, fostering social attitudes should be carried out continuously and integrated into all learning activities.